Biochemical and structural elucidation of the L-carnitine degradation pathway of the human pathogen Acinetobacter baumannii - Piskol, Fabian; Lukat, Peer; Kaufhold, Laurin; Heger, Alexander; Blankenfeldt, Wulf; Jahn, Dieter; Moser, Jürgen (Frontiers in Microbiology, 2024)
Acinetobacter baumannii is an opportunistic human pathogen which can use host-derived L-carnitine as sole carbon and energy source. Recently, an L-carnitine transporter (Aci1347) and a specific monooxygense (CntA/CntB) for the intracellular cleavage of L-carnitine have been characterized. Subsequent conversion of the resulting malic semialdehyde into the central metabolite L-malate was hypothesized. Alternatively, L-carnitine degradation via D-malate with subsequent oxidation into pyruvate was proposed. Here we describe the in vitro and in vivo reconstitution of the entire pathway, starting from the as yet uncharacterized gene products of the carnitine degradation gene operon. Using recombinantly purified enzymes, enantiomer-specific formation of D-malate by the NAD(P)+-dependent malic semialdehyde dehydrogenase (MSA-DH) is demonstrated. The solved X-ray crystal structure of tetrameric MSA-DH reveals the key catalytic residues Cys290 and Glu256, accessible through opposing substrate and cofactor funnels. Specific substrate binding is enabled by Arg166, Arg284 and Ser447 while dual cofactor specificity for NAD+ and NADP+ is mediated by Asn184. The subsequent conversion of the unusual D-malate reaction product by an uncharacterized NAD+-dependent malate dehydrogenase (MDH) is shown. Tetrameric MDH is a β-decarboxylating dehydrogenase that synthesizes pyruvate. MDH experiments with alternative substrates showed a high degree of substrate specificity. Finally, the entire A. baumannni pathway was heterologously reconstituted, allowing E. coli to grow on L-carnitine as a carbon and energy source. Overall, the metabolic conversion of L-carnitine via malic semialdehyde and D-malate into pyruvate, CO2 and trimethylamine was demonstrated. Trimethylamine is also an important gut microbiota-dependent metabolite that is associated with an increased risk of cardiovascular disease. The pathway reconstitution experiments allowed us to assess the TMA forming capacity of gut microbes which is related to human cardiovascular health.